he Impact of Employees’ Personality on their Psychological Contract in Fabric Manufacturing Industry of Sri Lanka - Ranasinghe, V.R.; Kottawatta, K.H.H. (My University, 2016)
Area of the Study This study seeks to the explore impact of employees‟ personality on their psychological contract in fabric manufacturing industry of Sri Lanka. Problem of the Study The research problem of this study is: Does the personality of the employees have an impact on their psychological contract in fabric manufacturing industry of Sri Lanka? Method of the Study The data were collected from a stratified sample of 196 executive employees in selected fabric manufacturing companies of Sri Lanka and used a structured questionnaire consisting 64 questions with 5 points Likert Scale. Data were analyzed through SPSS computer package and it included univariate analysis and bivariate analysis. Findings of the Study The findings of the study are that extroversion, agreeableness, conscientiousness and openness to experience except neuroticism were negatively and strongly correlated with the transactional psychological contract of executives. And extroversion, agreeableness, conscientiousness and openness to experience except neuroticism were positively and strongly correlated with the relational psychological contract of executives. As the multiple regression analysis, 94.1% of the variation in big five factors explained by the transactional psychological contract and 93.6% of the variation in big five factors explained by the relational psychological contract. Conclusion of the Study It is concluded that personality is an important variable to understand the psychological contracts. This study provides support for filling the gap of theoretical and practical understanding of personality and psychological contract in fabric manufacturing industry which is mainly helpful to retain talents within the organization even though there is a huge market competition.
Keywords: Personality; Big Five Personality Factors; Psychological Contract